2015
DOI: 10.1016/j.buildenv.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Topographical optimisation of single-storey non-domestic steel framed buildings using photovoltaic panels for net-zero carbon impact

Abstract: optimisation of single-storey non-domestic steel framed buildings using photovoltaic panels for net-zero carbon impact. Building and Environment, 86, 120-131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…McKinstray et al (2015aMcKinstray et al ( , 2016 conducted the design optimisation of long-span steel portal frames using fabricated beams to Eurocode 3, including topological asymmetry. The optimisation of single-storey non-domestic steel framed buildings using photovoltaic panels for net-zero carbon impact was also considered (McKinstray et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…McKinstray et al (2015aMcKinstray et al ( , 2016 conducted the design optimisation of long-span steel portal frames using fabricated beams to Eurocode 3, including topological asymmetry. The optimisation of single-storey non-domestic steel framed buildings using photovoltaic panels for net-zero carbon impact was also considered (McKinstray et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…The indoor environment of buildings is very complicated, and is a discontinuous, nonlinear, and distributed parameter system with high uncertainty. NSGA-II is suitable for such optimization issues [22,23].…”
Section: Multi-objective-based Optimization Algorithmmentioning
confidence: 99%
“…For steel portal frames, a recent paper [1] has shown that asymmetric shapes with photovoltaic (PV) panels on the southward side were advantageous for a low energy driven design. Asymmetry and PV panels allowed for reduced embodied energy solutions (less insulation) to achieve zero carbon standing by increased PV renewable space.…”
Section: Introductionmentioning
confidence: 99%
“…This present paper now investigates the effect of asymmetry [1] on the structural design optimisation with photovoltaic panels on the southward side of weight 0.4 kN/m 2 . Two frame configurations are considered; symmetric frames and asymmetric frames with an apex ratio of 0.8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation